Attitudes toward GM foods, biotechnology R&D investment and lobbying activities among agribusiness firms in the food, feed, chemical and seed industries in China. Issue 3 (4th September 2017) - Deng, Haiyan; Hu, Ruifa; Huang, Jikun; Pray, Carl; Jin, Yanhong; Li, Zhonghua
Abstract : Purpose: Economic interest groups such as seed, pesticide, feed, and food companies play an important role in supporting or preventing the production of genetically modified (GM) crops. The purpose of this paper is to examine firm managers' attitudes toward GM technology, biotechnology R&D investment, and political lobbying activities. Design/methodology/approach: Using data from surveys of 160 managers in the food, feed, chemical, and seed industries in 2013-2014, this paper employed three probit models to examine the determinants of managers' attitudes, biotechnology R&D investment, and lobbying activities. Findings: The results show that most Chinese agribusiness managers are concerned about GM foods and oppose its adoption. Nevertheless, one-third of the firms invest in biotechnology R&D and less than 15 percent of managers lobbied the government to change biotechnology policies. The econometric estimation results suggest that profit change expectation is the main factor affecting managers' attitudes and biotechnology R&D investment decisions, whereas lobbying activities are significantly influenced by their attitudes and biotechnology R&D investment. In addition, managers' attitudes toward GM foods also significantly influence firms' decisions to invest in biotechnology R&D. Originality/value: This paper has improved on previous research in two ways. First, it analyses the determinants of agribusiness firm managers' attitudes toward GM technology, biotechnology R&D investment, and lobbying activities. Second, the methodology involves an analysis of agribusiness firm survey data in the food, feed, chemical, and seed industries, which is the first time to use such data to research on economic interest group in agricultural biotechnology field.